Is correction of segmental kyphosis necessary in single-level anterior cervical fusion surgery? An observational study - Lu J; Sun C; Bai J; Tian S; Zhang B; Tian D; Kong L (Dove Medical Press, 2018)
Jian Lu,1,* Changjun Sun,2,* Jiangbo Bai,1,* Siyu Tian,1,* Bing Zhang,1 Dehu Tian,1 Lingde Kong1 1Department of Orthopedics, The Third Hospital of Hebei Medical University, Shijiazhuang, Hebei 050051, China; 2Department of Emergency, The Second Hospital of Tangshan City, Tangshan, Hebei 063000, China *These authors contributed equally to this work Background: This study was conducted to determine whether sagittal lordotic alignment and clinical outcomes could be improved by the correction of segmental kyphosis after single-level anterior cervical discectomy and fusion (ACDF) surgery.Patients and methods: We retrospectively reviewed patients who underwent single-level ACDF surgery in our hospital between January 2014 and February 2017. Basic characteristics of patients included age at surgery, gender, diagnosis, duration of symptoms, and location of target level. Pre- and postoperative radiographs at the 6-month follow-up were used to evaluate the following parameters, such as segmental angle, C2–C7 angle, T1 slope, and C2–C7 sagittal vertical axis (SVA). Postoperative clinical outcomes were assessed by the Neck Disability Index and VAS. According to the segmental angle of postoperative radiographs, patients were divided into noncorrection group and correction group.Results: A total of 181 patients (99 males and 82 females) were analyzed in our study. There were 32 patients in the noncorrection group and 149 patients in the correction group. There was no significant difference in demographic and clinical data between the two groups before surgery. However, patients in the correction group showed larger C2–C7 angle and lower C2–C7 SVA after surgery in comparison with those in the noncorrection group. Besides, changes in the segmental angle were positively correlated with changes in C2–C7 angle and negatively correlated with changes in C2–C7 SVA.Conclusion: Surgical correction of segmental kyphosis in single-level cervical surgery contributed to balanced cervical alignment in comparison with those without satisfactory correction. However, we could not demonstrate that the correction of segmental alignment is associated with a better recovery in clinical outcomes. Keywords: segmental kyphosis, sagittal alignment, single level, cervical spine, anterior cervical discectomy and fusion